077 Acute monoplegia. (23rd August 2021) - Lefever, Kristen; Eisemann, Jared; Gore, Letitia; Clarke, Laura; O'Gorman, Cullen; Swayne, Andrew; Schweitzer, Daniel
Abstract : Objectives: Pyomyositis is a purulent infection of skeletal muscle, most commonly resulting from haematogenous spread of Staphylococcus aureus infection in immunocompromised individuals 1 . Early recognition and management is important to prevent dissemination of infection and associated complications, including death. Methods: Single case report. Results: 63year old female represented to the emergency department with a three day history of a painful left arm, radiating from the neck. More recently, she had developed proximal left arm weakness and paraesthesia. She had suffered from a self-resolving diarrhoeal illness in the 48hours prior. Clinical examination confirmed a proximal left arm weakness of lower motor neuron pattern. Initial investigations demonstrated a normal creatinine kinase (CK) and white cell count, but elevated inflammatory markers. MRI cervical spine imaging excluded degenerative disease but raised suspicion of oedema within the left sided posterior cervical musculature. Subsequent blood cultures isolated methicillin sensitive Staphylococcus aureus. The patient developed lower back pain and fevers prompting further imaging, demonstrating multifocal epidural abscesses. There was no evidence of infective endocarditis. She received six weeks of intravenous flucloxacillin, followed by oral therapy, resulting in normalization of her inflammatory markers. Delayed repeat MRI imaging confirmed resolution of the epidural infection and improvement in left shoulder musculature oedema and hyperenhancement, which correlated with marked clinical improvement. Conclusion: Pyomyositis is increasingly recognised in temperate climates and immunocompetent individuals. Pain is an early feature, with CK often remaining normal throughout the disease. 1 2 Pyomyositis should be considered as a differential diagnosis in all patients with new onset painful weakness. References: Crum. Bacterial pyomyositis in the United States. The American Journal of Medicine 2004;117 :420–428. Bickels, Ben-Sira, Kessler, Wientroub. Primary pyomyositis. The Journal of Bone and Joint Surgery 2002;84 :2277–2286.